Increasing the efficiency of the membrane filtration process in the production of fruit and berry juices - Deynichenko, Grigory; Dmytrevskyi, Dmytro; Honchar, Dmutro; Piddubnyi, O. A.; Lavreniuk, V. V.; Дейниченко, Григорій Вікторович; Дмитревський, Дмитро В’ячеславович; Гончар, Дмитро; Піддубний, Олександр; Лавренюк, Владислав (Запоріжжя : Видавничій дім "Гельветика", 2025)
EN: The article considers the issue of increasing the efficiency of the membrane filtration process in the production of fruit and berry juices, which is a relevant direction in the development of modern technologies in the food industry. Membrane filtration, as a reagent-free and energy-saving method of processing liquid food products, allows you to obtain high-quality juices with minimal losses of biologically active substances and without deterioration of organoleptic indicators. The paper presents a generalized scheme of the membrane filtration technological process, characterizes the main stages – raw material preparation, enzymatic treatment, preliminary filtration, the main stage of membrane separation, membrane washing and stabilization of the finished product. The influence of the main technological parameters – operating pressure, temperature, cross-flow velocity and membrane type – on the efficiency of the process and the quality of the filtrate is analyzed. It was established that the optimal conditions for ultrafiltration of fruit and berry juices are a pressure of 0.3…0.6 MPa, a temperature of 25…35 °C and a flow rate of 1.5…2.5 m/s, under which the highest productivity is achieved with minimal membrane contamination. It was shown that enzymatic preparation of raw materials provides a decrease in viscosity and an increase in filtration speed, and the use of membranes with antifouling properties and a modified surface contributes to stable system operation. The results obtained confirm the feasibility of an integrated approach to optimizing the membrane filtration process, which involves simultaneous improvement of technological parameters, the design of membrane devices and membrane cleaning systems. The use of such solutions allows to ensure high quality of the final product, reduce energy and operating costs, and also increase the environmental efficiency of production. The results of the study are of practical importance for juice industry enterprises that implement modern technologies of membrane cleaning and product concentration. /// UA: У статті досліджено шляхи підвищення ефективності процесу мембранної фільтрації у виробництві плодовоягідних соків. Розглянуто переваги застосування мембранних технологій як енергоощадного й екологічно безпечного методу очищення, що дає змогу отримати високоякісні соки без трати природних властивостей. Описано основні етапи технологічної схеми: підготовку сировини, ферментативну обробку, попереднє фільтрування, основну мембранну фільтрацію, промивання мембран і стабілізацію готового продукту. Проведено аналіз впливу ключових технологічних параметрів – тиску, температури, швидкості потоку та типу мембрани – на швидкість і стабільність процесу. Встановлено, що оптимальні умови для ультрафільтрації становлять тиск 0,3…0,6 МПа і температуру 25…35 °С, що забезпечує високу продуктивність та мінімальне забруднення мембран. Зазначено, що попередня ферментативна обробка сировини підвищує ефективність процесу, а використання антифолінгових мембран сприяє продовженню їх терміну служби. Результати дослідження підтверджують ефективність комплексного підходу до вдосконалення мембранної фільтрації, який дає можливість покращити якість соків, зменшити енергоспоживання та підвищити екологічну стійкість виробництва.
Підвищення ефективності процесу мембранної фільтрації у виробництві плодовоягідних соків
Keywords: membrane filtration; fruit and berry juices; ultrafiltration; purification; membrane selectivity; product quality; technological parameters; мембранна фільтрація; плодовоягідні соки; ультрафільтрація; очищення; селективність мембран; якість продукту; технологічні параметри